Analisis pengaruh Gross Domestik Product (GDP) dan Suku Bunga (SB) terhadap Foreign Direct Investment (FDI) pada periode tahun 2012-2019 - Heri Gunawan; Alexandro Yohan Enrico; Aldi Bagas Satria; Tb. M Farhan Hidayat (Peneliti.net, 2023)
FDI is foreign investment made from foreign companies that invest their capital into the country from this study to analyze how and to what extent the analysis of the influence of Gross Domestic Product (GDP) and Interest Rates (SB) on Foreign Direct Investment (FDI) in the 2012 period -2019. This study uses multiple regression analysis with panel data as the method of analysis. This study focuses on Indonesia as cross-sectional data and the time span between 2012 and 2019 as time series data. This study aims to analyze the influence of the analysis of the influence of Gross Domestic Product (GDP) and Interest Rates (SB) on Foreign Direct Investment (FDI).